EL POSMODERNISMO: UN APAGÓN CULTURAL HISTÓRICO - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
Abstract. The posmodernismo is the intellectual fashion of the present time. The great dreams collapsed. The socialism, instead of being fruit of the childbirth of an exhausted and dying society, constituted the abortion of a global society. Of the heroic revolutions it is not nothing. Capitalism lacks alternative today. Sufficient reason like for a strong collective depression and factor of frustration. Resumen. El posmodernismo es la moda intelectual de actualidad. Por cierto, esto no es casual. Responde a un "estado de ánimo". Entrega un modelo de las formas de pensar del fin de siglo, de las formas de aprehender la realidad. Más concretamente, articula la autojustificación de las actitudes y prácticas de la gran mayoría de los intelectuales en el presente.